Views of UK renal patients regarding deceased organ donation - Theodosopoulou, M; Dor, F; Rituerto, D; Athanasiou, T; Baskozos, G; Pusey, C; Papalois, V (Wiley, 2017)
This research focuses on Deceased Organ Donation (DOD) not only as an isolated individual decision, made by the individual and affecting solely that individual, but as a decision, which is made within a social context and influenced by it. This research project focuses on health literacy practices of renal patients regarding DOD.